2021
DOI: 10.4103/ua.ua_144_19
|View full text |Cite
|
Sign up to set email alerts
|

Male sexual function after weight-loss surgeries in a group of Saudi population

Abstract: Introduction: Obesity is associated with erectile dysfunction in many studies. This study aims to inspect the impact of weight-loss surgery on the erectile function in the Saudi male population. Patients and Methods: Forty-two consecutive male patients who underwent weight-loss surgery during a period from February 2013 to July 2016 were included in the study. Unmarried patients were excluded from the study. A designed questionnaire includes the short version of the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Abnormal EF, also known as ED, is defined as scores of EF ≤25 ( 20 ). According to Sexual Health Inventory for Men (SHIM), scores of EF ranging from 22 to 25 are classified as mild ED, 17–21 as mild to moderate ED, 11–16 as moderate ED, ≤10 as severe ED ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal EF, also known as ED, is defined as scores of EF ≤25 ( 20 ). According to Sexual Health Inventory for Men (SHIM), scores of EF ranging from 22 to 25 are classified as mild ED, 17–21 as mild to moderate ED, 11–16 as moderate ED, ≤10 as severe ED ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The advances in sexual function were accompanied by favorable changes in metabolic conditions. Recent studies applying the IIEF questionnaire revealed that bariatric surgeries positively impacted sexual function in men with obesity 1 year postoperatively in different countries (8,21,23,29,30). Mora et al (33) found that DBMI had positive correlations with DIIEF and DEF, concluding that weight loss is the major contributor to improved sexual function.…”
Section: Impact Of Bariatrics On Sexual Functionmentioning
confidence: 99%
“…2. Surgical weight reduction improves the profile of male sex hormones, leading to an increase in the level of total testosterone, free testosterone, and sex hormone binding globulin and lowers the concentration of oestradiol [37,38,[43][44][45][46][47][48][49][50][51][52][53]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies assessing the IIEF, it has improved compared to the condition before surgery. More research is needed on the direct effects of bariatric surgery on sexual function in multiple domains [37,38,[43][44][45][46][47][48][49][50][51][52][53]. 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation